PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. TIGA TUNAS ALTA JAKARTA BARAT - Siti Nuralifah; Syawaludin (Journal of Research and Publication Innovation, 2025)
This research aims to analyze the influence of the work environment and motivation on employee performance at PT. Tiga Tunas Alta West Jakarta, both partially and simultaneously. The method used is quantitative by collecting data through questionnaires filled in by 60 respondents. Data analysis techniques include simple linear regression tests, multiple linear regression, as well as t tests and f tests. The research results show that the work environment has a significant effect on employee performance, with a regression equation Y = 10.064 + 0.785X, The t test shows the t-count of 8.733 which is greater than the t-table of 1.661 with a significance value of 0.000 < 0.05. Motivation also has a significant effect on employee performance, with a regression equation Y = 15.975 + 0.655X, The t test for Motivation produces a t-count of -1.825, which is smaller than the t-table of 1.661 with a significance value of 0.073 > 0.05. Simultaneously, the Work Environment and Motivation have a significant effect on Employee Performance, with a regression equation Y = 8.812 + 0.459X1 + 0.362X2, The results of the f test show that the F-count is 38.345 which is greater than the F-table of 3.16 with a significance value of 0.000 < 0.05.